PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA USAHA BISNIS KULINER CAFÉ - Sri Yanthy Yosepha; Siti Azizah Latifah Dinar (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Cafe is a culinary business that is currently being established everywhere, not only students and students flock to the cafe to relax and do their assignments, but even businesspeople also choose cafes as a place to meet their colleagues. Customersatisfaction is strongly influenced by the quality of service provided by the café, so the café must provide the best quality in serving customers in achieving customer satisfaction. Customer satisfaction with cafe services is an evaluation of cafemanagement in maintaining or improving service quality. This study aims to determinethe effect ofservice quality on customer satisfaction in the culinary cafe business. This study uses a literature review of several previous research results in Indonesia. Journalsearch sources via Google Scholar in the period 2014 – 2022. The results showed that service quality was measured using 5 dimensions, namely Reliability, Tangibles,Responsiveness, Assurance, and Empathy. Studies show that service quality influencescafé customer satisfaction